Projeto de vida e ENEM : uma análise do questionário socioeconômico e suas implicações para o ensino médio - Anjos, Tiago Ribeiro dos (2017)
This work has the objective of analysing the relationship between the interest of participating in the entrance test, considering social, economic and racial aspects and the building of a life plan of teenagers from public and private schools of the state of São Paulo. In order to comprehend the relationship previously mentioned, we used the data for the answers of the socioeconomic survey of applicants for the 2012 exam in the state of São Paulo. The database containing the answers that refer to the interest in participating in the exam are made available by INEP and were processed using statistical software SPSS version 17. Altogether, seven questions were selected and grouped into three categories: (i) The ENEM as a possibility of self-knowledge; (ii) The ENEM as a possibility for social development; relationship with work and (iii) The Enem as a possibility to enter higher education. As a result of this study, it was possible to verify significant differences between the responses of students from social classes and racial profiles, showing that inequality in Brazil, especially racial inequality, is embodied in the interest of adolescents, thus becoming an institutionalized phenomenon.